Kehadiran Gembala sebagai Bentuk Pengorbanan: Studi Teologis Yohanes 10:11–15 dalam Konteks Pelayanan Pastoral Moderneologis Yohanes 10:11-15 dalam Konteks Pelayanan Pastoral Modern - Wennar; Santosa, Rivosa (STT Internasional Harvest Tangerang, 2025)
This study examines the meaning of the shepherd’s sacrifice in John 10:11–15 by highlighting the close relationship between sacrifice and relational presence. Interpretations of the statement “the good shepherd lays down his life for the sheep” are often confined to a soteriological horizon, referring primarily to Jesus’ death on the cross. Through narrative and lexical exegesis, this study demonstrates that the Gospel of John constructs the meaning of sacrifice within the framework of a shepherding relationship marked by presence, mutual knowing, and faithfulness to the flock. By employing a psychological biblical interpretation approach, the shepherd–sheep metaphor is read as a depiction of a relationship that responds to existential vulnerability, in which the shepherd’s presence fosters a sense of security and relational attachment. Christological elaboration affirms that such presence constitutes an integral expression of Jesus’ identity as the Good Shepherd, rather than merely a pastoral function or strategy. The critique of the “hired hand” figure reveals that authentic shepherding is determined by the quality of relationship rather than by the continuity of function or structure alone. This study also outlines the theological and pastoral implications of understanding sacrifice as presence for contemporary church ministry